If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 23 + 9 = 4b + 66 Combine like terms: 23 + 9 = 32 32 = 4b + 66 Reorder the terms: 32 = 66 + 4b Solving 32 = 66 + 4b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-4b' to each side of the equation. 32 + -4b = 66 + 4b + -4b Combine like terms: 4b + -4b = 0 32 + -4b = 66 + 0 32 + -4b = 66 Add '-32' to each side of the equation. 32 + -32 + -4b = 66 + -32 Combine like terms: 32 + -32 = 0 0 + -4b = 66 + -32 -4b = 66 + -32 Combine like terms: 66 + -32 = 34 -4b = 34 Divide each side by '-4'. b = -8.5 Simplifying b = -8.5
| 2m^7-7m+6=0 | | 2x-7=1x-2 | | 0.5x+11-x=0.6x+0.3 | | 6+6r=66 | | 15=0.6f | | 2w+6=10 | | 5(m-3)-4(m+2)=-23 | | 4+105x+5=-0.08571428571 | | (2x^2)+13x=180 | | 5x-(x+4)=8 | | 6x+25-6x=35 | | 1+3y=16 | | 2(3x+6)=-49+19 | | z+9/=2.1 | | 10-4s+2s= | | N+(-16)=0 | | 24a-24= | | 5z+3=5z-z | | -3a+7+4a=16-25 | | 14+7y-5= | | 5r-5s=0 | | 10x+72=23x+6 | | 3(m-2)+5=8-2(m-4) | | 3+3r=9 | | 4x+6=-1x+1 | | 17+3(c-2)-11c=-7(c+2)+14 | | 3x+5x=19+5 | | 9-K=k+3 | | 2x+z=7 | | (u+5)/8=2 | | X+14+19(3)=17 | | 1.8+9=5.7-6 |